Soil management in semi-arid vineyards: Combined effects of organic mulching and no-tillage under different water regimes - Buesa, Ignacio; Miras-Ávalos, José M.; De-Paz, José M.; Visconti, Fernando; Sanz, Felipe; Yeves, Antonio; Guerra, Diego; Intrigliolo, Diego S. (Elsevier, 2021)
Optimizing water use in vineyards is crucial for ensuring the sustainability of viticulture in semi-arid regions, and this may be achieved by minimizing direct water evaporation from the soil through the use of mulching. In this context, the current study aimed at assessing the combined effects of the vine-row application of an organic mulch (vine prunings) and no-tillage under two water regimes on soil properties, plant water and nutritional status, yield and must composition of grapevine (Vitis vinifera L.) cv. Bobal grown under semi-arid conditions. For this purpose, a field experiment in a split-plot design was carried out for three years (2016–2018) in a mature Bobal vineyard located in Eastern Spain. Two soil management strategies (tillage and organic mulching with no-tillage) were assessed under two water regimes (rainfed and deficit drip irrigation) with four replications per combination. Vine responses were determined by measuring midday stem water potential, leaf nutrient concentrations, pruning weight, yield components and grape composition. Soil properties were assessed at the end of the experiment. Mulching and no-tillage positively affected vine water status under both water regimes, resulting in reductions in grape phenolic composition. Interactive effects of both water regime and soil management on water use efficiency were found. Regardless of soil management practice, irrigation increased yield and pruning weight when compared to rainfed conditions. Soil management had slight effects on vine nutritional status. At the end of the experiment, soil compaction increased and infiltration decreased as a consequence of mulching and no-tillage. Organic mulch and no-tillage improved vine water status, however, considering the final soil surface compaction and low water infiltration rate, longer-term studies are necessary to assess the sustainability of combining both practices.